FOREIGN AID AND THE STABILITY OF WEST AFRICAN GOVERNMENTS AND MILITARY COUPS: THE BURKINA FASO'S EXPERIENCE - Ebimnamaonye, Herbert Chukwudi (PT. Antis International Publisher, 2026)
Objective: This paper explored how foreign aid influences the stability of the West African governments and military coups with specific reference to Burkina Faso. The research thus sought to explore the question of whether foreign aid had empowered the institutions of governance or led to political instability and unconstitutional governmental transitions. Method: The research was based on the Dependency Theory, which was developed by Andre Gunder Frank (1966; 1967). The research methodology used was qualitative. Secondary sources were used to get data, including textbooks, academic journal articles, government publications, newspapers, and international news sources. Content analysis was used to analyse the data in order to determine patterns and relationships between foreign aid, governance stability, and military coups in Burkina Faso. Results: The results indicated that foreign aid had helped in certain areas of governance by providing administrative support, development programmes, humanitarian aid, and security cooperation. These gains, however, failed to translate into long term political stability and popular legitimacy. The study discovered that aid was more successful in situations where institutions were already in place, but in Burkina Faso weak governance structures, insecurity and low levels of state legitimacy diminished the value of aid in stabilising situations. Novelty: The research found that foreign aid had reinforced the remnants of the state, but not the political legitimacy and institutional stability needed to achieve stable democratic governance in Burkina Faso. The study suggested more powerful domestic institutions, more people-oriented aid interventions, and less reliance on external assistance by mobilising domestic resources.